EVALUATING THE ANTI-INFLAMMATORY POTENTIAL OF GAMMA ORYZANOL FROM ORYZA SATIVA BY TARGETING THE NF-KB PATHWAY: A MOLECULAR DOCKING AND STRUCTURE-BASED PHARMACOPHORE MODELING APPROACH - Aasia, Kanwal; Muhammad Hamdi, Mahmood; Saiful Bahri, Talip; Norhida, Ramli (Innovare Academic Sciences Pvt Ltd, 2026)
Objective: The nuclear factor kappa-B (NF-κB) pathway is a key regulator of inflammation observed in polycystic ovary syndrome (PCOS), rendering it a promising target for treatment. Gamma oryzanol (γ-oryzanol) has been reported to display anti-inflammatory properties. However, the particular γ-oryzanol compounds and their specific molecular mechanism by which γ-oryzanol interacts and modulates NF-κB activity have yet to be explained. The study intended to explore the molecular interactions underlying the anti-inflammatory activity of γ-oryzanol against NF-κB through in silico molecular docking and structure-based pharmacophore modeling. Methods: A receptor-based pharmacophore model was created from the ligand-binding site of the NF-κB through the Molecular Operating Environment 2019 software. The pharmacophore comprised four features: one hydrogen bond donor, one hydrogen bond acceptor, one aromatic, and one hydrophobic feature. The optimized model was used to screen an in-house phytochemical database to find the hit compounds with matching features, followed by molecular docking of hit compounds to evaluate their binding manners and interactions with NF-κB. The docking poses were analyzed for key interactions and ranked based on their docking scores. Results: Four lead compounds that satisfied the pharmacophore query were 24-methylenecycloartenyl ferulate, cycloartenyl ferulate, campesteryl ferulate, and β-sitosteryl ferulate. The docking results showed that 24-methylenecycloartenyl ferulate had the most potent interaction with NF-kB (-6.9 Kcal/mol), followed by cycloartenyl ferulate (-6.7 Kcal/mol), campesteryl ferulate (-5.9 Kcal/mol), and β-sitosteryl ferulate (-5.1 Kcal/mol), indicating their potential to modulate NF-κB. Conclusion: The present study provides molecular insights into the potential modulatory mechanism of γ-oryzanol against NF-κB. γ-oryzanol, along with structurally related phytochemicals, may serve as a promising scaffold for targeting NF–κB–mediated inflammation, implicated in PCOS. These computational predictions offer a foundation for experimental validation in related inflammatory disease models.